Pulmonary Function Assessment with Spirometry in Symptomatic Post-COVID-19 Patients: A Cross-Sectional study at Dhaka Medical College Hospital - Sultana, Sharmin; Ahmad, Md Mohiuddin; Kamal, Hena; Hossain, Md Bellal; Sarkar, Nirmal Kanti; Sen, Goutom; Afroze, Sharmin; Mahmud, Md Miraz (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: The emergence of COVID-19 has posed challenges in managing the disease and mitigating its long-term effects, particularly on the respiratory system. This study assessed lung function abnormalities through spirometry in symptomatic post-COVID-19 patients in a tertiary care hospital in Bangladesh. Methods: This cross-sectional study was conducted at Dhaka Medical College Hospital over one year. A total of 100 post-COVID-19 patients with shortness of breath and/or cough 6-8 weeks post-discharge were included. Patients underwent face-to-face interviews, clinical history reviews including previous investigations findings and spirometry tests. Spirometry assessments were classified as normal or restrictive. The severity of restrictive changes were graded from mild to very severe. FEV1 and FVC were measured, and the FEV1/FVC ratio was calculated. Data were analyzed using SPSS Version 25. Results: The mean age of participants was 51.3±7.27 years, with a male predominance (70% male). Common symptoms included cough (86%), shortness of breath (54%), and weakness (41%). Spirometry showed that 66% had restrictive changes, with mean FEV1 at 61.04±10.69% and FVC at 73.02±12.73%. Restrictive changes in spirometry were significantly predominant in severe COVID-19 cases (p<.05) and were associated with pre-existing conditions like hypertension, diabetes, and smoking history (p<.05). Logistic regression revealed higher odds of restrictive changes with older age, smoking history, disease severity, and the presence of diabetes and hypertension. Conclusion: This study reported a high prevalence of restrictive changes in spirometry in post-COVID-19 patients, associated with disease severity and pre-existing comorbidities. J Bangladesh Coll Phys Surg 2025; 43: 13-19